A Comparative Analysis of Pre-Trial Procedure in Europe: The Search for an Ideal Model. - Johnston, Edward; Erbas, Rahime; Jasinski, Dan (Istanbul University Press, 2020)
The hearing of a case in a court room by a tribunal, today classified as the trial phase, has long stood inherently in the nature of the judicial competence of a State. By contrast, the pretrial phase and the introduction of the public prosecutor into the criminal procedural system as a subject of the judicial process has a much shorter history than the trial. However, in recent times, the pre-trial process has arguably been the subject of more heated debates than the trial phase has been. One reason for this, is that the pre-trial process is one which begins with a simple suspicion and subsequently seeks to reach a certain degree of suspicion so that indictment can be introduced to the court by prosecutor. Despite the existence of uncertainty as whether sufficient evidence required in order introduce the indictment to the court will be established, the main fundamental rights and freedoms, inter alia, freedom of liberty and right to privacy can be intervened by the public prosecutor and even police officers at a very early stage in of a criminal case, in all jurisdictions covered by this book. This clearly places core protections, such as presumption of innocence, at risk of harm. This raises an interesting disjunction, whereby on the one hand, at pre-trial stage the degree of suspicion required to deprive a suspect's liberty is lower than it is in trial, on the other, the fundamental rights and freedoms are at increased risk of violation in the pre-trial stage.Another notable feature of the pre-trial phase across Europe, is its dependence on the thematic underpinnings of the national approach to criminal procedure rules, perhaps most notably, whether they are deeply rooted in adversarial or inquisitorial traditions, or one of the infinite possible combinations of those two ideals. In other words, the way in which a criminal justice system approaches to rights and freedoms of the suspects in the pre-trial phase is shaped by their expectations and reservations to the role of the suspect. For instance, the right to access legal assistance features less in systems that are more closely connected to inquisitorial ideals than adversarial. Because the public prosecutor regarded as a paramount, in Lat. dominus litis, who aims to find out the material truth has to collect all evidence, whether it bolsters or undermines the case against the suspect. Therefore, the role of the prosecutor, and in some jurisdictions the police, in collecting and controlling the evidence, has been seen as a justification for the proceedings in the pre-trial and the defence lawyer can xii exercise a diminished role. What's more, the pre-trial phase places much more emphasis on inquisitorial ideals than it does adversarial. Because inquisitorial system seeks to find out the material truth by focusing on a case rather than a person as partisan interest. Consequently, the importance of the gathering evidence in that stage is self-evident.This edited collection brings together analyses of the pre-trial process across a number of European jurisdictions together, proffering the opportunity for readers to draw comparisons among them, in order to reach an ideal model of pre-trial procedure. To that end, this edited collection examines the pre-trial procedure in a number of different jurisdictions throughout Europe. Covering a number of key topics, such as the arrest thresholds, the roles of key actors in the process, the limits on the investigation and the rules surrounding the decision to charge, the book critically analyses the safeguards that exist throughout this process, the rights of the suspect as well as the impact of the statements made during the investigative stage. Finally, it examines the impact illegally obtained evidence holds for the trial process.In that respect, the book provides ten distinctive chapters from jurisdictions including Croatia, England and Wales, Estonia, Germany, Italy, North Macedonia, Serbia, Spain, The Netherlands and Turkey. The title of each chapter depicts the relevant jurisdiction and the focus on system of pre-trial on a given jurisdiction. However, some authors have chosen to deal with specific challenges that can be found within a particular jurisdiction. For example, a number of authors have focussed on the benefits and tribulations brought about by recent reforms, such as that in Croatia. Other's as the chapter from The Netherlands focusses on the uniquely fundamental role of the case-file and or German colleagues present interesting arguments surrounding so called 'cash for justice' issues. The youth and inexperience of duty defence lawyers is highlighted as a particular issue in Turkey. The Italian chapter indicates the transformation of Italian criminal justice system from inquisitorial to adversarial approach, starting in 1988. Moreover, both the Italian and German chapters address a significant and permanent topic: the discretion of the prosecutor to conclude the case without trial and respectively penal order issue. In conjunction with that, readers will observe the relationship between police and prosecutor through the empirical date in Serbian chapter. It deals with the tension between the role of the prosecutor as a guarantor for ensuring fundamental rights and freedoms in prosecuting crimes and the Police's operational independence, initiative and creativity in combating crime.The Spanish chapter highlights the strong place of the judge of instruction (juge d'instruction), a traditionally French concept, which is maintained in Spanish criminal xiii procedure. The Estonian chapter reveals that characteristics of Soviet rule remain in thier criminal procedure, even as an EU member state. Our North Macedonian colleagues present and overview of the pre-trial process in a compact way, providing an example of Western Balkan countries. The chapter from England and Wales chapter provides the reader, in particular those who are not non-familiar to common law criminal justice system, with analytical insights into an adversarial pre-trial process. Finally, the chapter from Turkey focuses on the early access to legal assistance in Turkey, with special regard paid to the case of Salduz v. Turkey, a landmark case of the ECtHR that has influenced pre-trial procedure in jurisdictions throughout Europe.In doing so, the book provides a comparative analysis on the pre-trial procedure within Europe that includes the comparison of a variety of themes, drawn together in a concluding chapter. These themes mainly consist of a historical, functional, legislative and cultural focus. In that regard, the readers will discover the influences that have shaped the criminal procedure in a particular jurisdiction, along with the rationale for the approach taken. It should be emphasized that the aims of this book is not to label particular jurisdictions 'good' or 'bad', but rather to allow readers to select elements of each jurisdiction in order to form their ideal model. Further, in a comparative study methodology, a fundamental discussion whether a comparativist should focus more on similarities or differences among jurisdictions exists.1 Rather, the editors prefer to take a pragmatic approach by comparing the jurisdictions covered in the book to find out unique and common practices with other jurisdictions in order to reach an ideal model for the creation a better pre-trial procedure system in Europe.